Procurement of works. - World Bank. (Washington, D.C. : World Bank, 2002)
Prepared for use by borrowers in the procurement of admeasurement (unit price or rate) type of work contracts through international competitive bidding. The procedures and practices presented in the document ave been developed through broad international experience and are mandatory for use in works contracts financed in whole or in part by the World Bank which are estimated to cost more than US$10 million.
"May 2000, revised March 2002."
oif 17/02/15
Loan
Keywords: World Bank -- Procurement -- Handbooks, manuals, etc; Contracts for work and labor -- Forms; Letting of contracts -- Forms; Industrial procurement